Aspek Linguistik Dalam Penerjemahan - Sriyono Sriyono (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2018)
Transferring one language into another in form and meaning is unavoidable in translation. Theory and practice in translation involve linguistics as means to comprehend the Source Language well. In addition, linguistics cannot be separated from translation since study and practice of translation is one of applied linguistics which involves system and meaning of language. Linguistics in terms of morphology, syntax and semantics contribute in determining equivalent in term of grammatically and semantically. Besides, studies in translation may  collaborate linguistics aspects in determining research area in translation. Therefore, linguistics aspects is one of  ways in solving many problems in translation research and translation practice.Keywords: translation, linguistics, morphology, syntax, semantics